2011
DOI: 10.1172/jci44564
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor activation reduces lipid synthesis in pancreatic islets and prevents β cell failure in rodent models of type 2 diabetes

Abstract: The failure of pancreatic β cells to adapt to an increasing demand for insulin is the major mechanism by which patients progress from insulin resistance to type 2 diabetes (T2D) and is thought to be related to dysfunctional lipid homeostasis within those cells. In multiple animal models of diabetes, females demonstrate relative protection from β cell failure. We previously found that the hormone 17β-estradiol (E2) in part mediates this benefit. Here, we show that treating male Zucker diabetic fatty (ZDF) rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
148
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(150 citation statements)
references
References 45 publications
(51 reference statements)
2
148
0
Order By: Relevance
“…[1][2][3] In a recent study, we reported that 17β-estradiol (E2) protects against T2D in male Zucker Diabetic Fatty (ZDF) rats and mice fed a highfat diet by suppressing islet lipogenesis and toxic lipid accumulation, thus preventing lipotoxic β-cell failure. 4 We found that islets from ZDF rats displayed an imbalance between lipid synthesis and utilization. This was characterized by increased islet lipogenesis unmatched by islet lipid oxidation and lipolysis, leading to an increase in islet free fatty acids (FFAs) and mono-, di-and triglycerides (MAG, DAG, TG) accumulation.…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…[1][2][3] In a recent study, we reported that 17β-estradiol (E2) protects against T2D in male Zucker Diabetic Fatty (ZDF) rats and mice fed a highfat diet by suppressing islet lipogenesis and toxic lipid accumulation, thus preventing lipotoxic β-cell failure. 4 We found that islets from ZDF rats displayed an imbalance between lipid synthesis and utilization. This was characterized by increased islet lipogenesis unmatched by islet lipid oxidation and lipolysis, leading to an increase in islet free fatty acids (FFAs) and mono-, di-and triglycerides (MAG, DAG, TG) accumulation.…”
mentioning
confidence: 74%
“…1B), demonstrating that RLX acts as an ER agonist in β-cells with regard to preventing TG accumulation. Since we observed that estrogens similarly suppressed lipogenesis in INS-1 cell, rodent and human islets, 4 we anticipate that RLX would also suppress TG accumulation in human islets. Thus, in β-cells, RLX behaves as an ER antagonist with regard to nuclear ERE-dependent actions and as an ER agonist with respect to extranuclear anti-lipogenic actions.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…A previous study reported that the binding of E 2 to the ER induces phosphorylation of signal transducer and activator of transcription 3 (STAT3), which reduces FAS expression in liver (Gao et al 2006;Tiano et al 2011). STAT3 has been shown to decrease TG synthesis, which is independent of the fatty acid synthesis pathway through SREBP1 (Kinoshita et al 2008).…”
Section: Discussionmentioning
confidence: 99%